2020
DOI: 10.1534/g3.120.401126
|View full text |Cite
|
Sign up to set email alerts
|

ngn-1/neurogenin Activates Transcription of Multiple Terminal Selector Transcription Factors in theCaenorhabditis elegansNervous System

Abstract: Proper nervous system development is required for an organism’s survival and function. Defects in neurogenesis have been linked to neurodevelopmental disorders such as schizophrenia and autism. Understanding the gene regulatory networks that orchestrate neural development, specifically cascades of proneural transcription factors, can better elucidate which genes are most important during early neurogenesis. Neurogenins are a family of deeply conserved factors shown to be both necessary and sufficient for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…These data suggest that ngn-1 affects the fate, axonal projection and position of the AIY neuron. Similar observations in ngn-1 mutants have been recently reported ( Christensen et al, 2020 ), however, in this study, the origin of these AIY neuron defects was not further analyzed.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These data suggest that ngn-1 affects the fate, axonal projection and position of the AIY neuron. Similar observations in ngn-1 mutants have been recently reported ( Christensen et al, 2020 ), however, in this study, the origin of these AIY neuron defects was not further analyzed.…”
Section: Resultssupporting
confidence: 79%
“…Another possibility is that NGN-1 binds egl-1 cis -regulatory regions and that the presence of a specific cofactor on egl-1 cis -regulatory regions turns NGN-1 into a repressor. Interestingly, a recent RNA sequencing study showed that the majority of differentially expressed genes in ngn-1 mutants are upregulated supporting the idea that NGN-1 may indeed be able to act as a repressor ( Christensen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 87%
“…Our analysis of basic helix-loop-helix (bHLH) transcription factors was originally motivated by our quest to understand how the expression of terminal selector transcription factors is controlled. Terminal selectors have emerged as key regulators of neuronal identity throughout the entire nervous system (Hobert, 2016), yet we understand little about how their expression is induced in the embryo (Baumeister et al, 1996;Bertrand and Hobert, 2009;Christensen et al, 2020;Mitani et al, 1993;Murgan et al, 2015). Based on a previously reported effect of lin-32 on the expression of the terminal selectors unc-86/Brn3 (Baumeister et al, 1996) and mec-3 (Mitani et al, 1993), we sought to investigate the role of lin-32 further.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cnd-1 functions close to the end of a transcriptional regulatory cascade during C. elegans embryogenesis. This is in contrast to ngn-1 /neurogenin, which controls expression of at least eight downstream transcription factors ( Christensen et al 2020 ).…”
Section: Resultsmentioning
confidence: 96%